1984
DOI: 10.1002/pros.2990050305
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of prostatitis in the rat

Abstract: A spontaneous, nonacute, age-dependent prostatitis was found in a high incidence in the lateral prostatic lobes of Lewis rats. Such rats were treated with methylprednisolone, indometacin , testosterone, hexyloxyphenylproprionate , polyestradiol phosphate, various antibiotics, or were caged together with female rats. The effect of the different treatment modalities was evaluated microscopically by blind observation of the degree of inflammatory reaction in the lateral prostate. Methylprednisolone and the testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Rat prostatitis is similar to the human condition and these findings support the hypothesis that corticosteroids should be further evaluated as a treatment option. 12 We were unsuccessful in finding any other references on a search of Medline, the Science Citation Index, Embase, or the Cochrane Library.…”
Section: Discussionmentioning
confidence: 99%
“…Rat prostatitis is similar to the human condition and these findings support the hypothesis that corticosteroids should be further evaluated as a treatment option. 12 We were unsuccessful in finding any other references on a search of Medline, the Science Citation Index, Embase, or the Cochrane Library.…”
Section: Discussionmentioning
confidence: 99%
“…Naslund et al5 reported that spontaneously-developed prostatitis and E2-induced prostatitis in Wistar rats had the same histologic findings. Other studies have demonstrated that spontaneous nonbacterial prostatitis in rats was histologically very similar to CP in humans 7,8…”
Section: Introductionmentioning
confidence: 88%
“…This is an inflammatory process localized primarily in the lateral lobe of the rat prostate, with which steroid hormones may be associated [86, 87]. Rats maintained on a soya-free diet for 11 weeks developed severe inflammation in the lateral prostate, whereas rats maintained on a diet with adequate soya, or commercial rat chow which contains soya, did not develop any signs of prostatitis.…”
Section: Prostatitis and Dietary Factorsmentioning
confidence: 99%